Perancangan Sistem Informasi Kasir Dengan Barcode Berbasis Web Dan Framework Codeigniter - Efit Pany (Jurnal Informatika, 2022)
This thesis aims to assist in how to design an application program in creating and the creation of a program that will be run. The cashier Information System with barcode is quite needed by wholesalers or supermarkets that are needed by the community quickly, accurately and integrated. The methodology used is UML (Unified Modeling Language). With the language used is PHP with codeigniter framework and database used MySQL, cashier Information System Design with barcode web-based data management information system produces goods or products that can facilitate the sales process without having to wait long in the transaction process.